Transformasi Digital Sektor Kesehatan Pada Telemedisin Indonesia - Samad, M. Yusuf; Brata, Taryana; Azzahra, Fatimah; Rosadi, Fajri; Permatasari, Diah Ayu; Krisdwiyanto, Nova Teguh (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
Digital transformation in the health sector in Indonesia has grown since the COVID-19 pandemic several years ago, one form of digital transformation is the emergence of telemedicine services in Indonesia. However, Indonesia's capacity and readiness are not yet adequate for realizing digital transformation because Indonesia needs to anticipate several risks that may occur in accelerating digital transformation, such as the potential for data misuse and privacy violations and the threat of cyberattacks. This article aims to identify the challenges and opportunities for digital transformation, especially telemedicine services in Indonesia. This article uses a qualitative approach with data sources from literature reviews. The results show that digital transformation in the health sector, especially telemedicine services, faces challenges from people, processes, and technology. However, training medical personnel, increasing system integration, and using protection technology are opportunities to improve patient data security and the efficiency of telemedicine services.